2016
DOI: 10.1007/s00404-016-4175-x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of the interleukin 6 gene and additional gene–gene interaction contribute to cervical cancer susceptibility in Eastern Chinese women

Abstract: Minor allele of rs1800795 and rs2069837 and its interaction were associated with increased cervical cancer risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 22 publications
0
18
1
Order By: Relevance
“…There are three articles about the association between rs2069837 and cancer risk, and their results consistently showed that the rs2069837-AA genotype was a protective factor for cervical cancer and hepatocellular carcinoma, one study found that rs2069837 were related to the IL6 expression level in cervical tissues. [36–38]. In our study the results were not statistically significant, further studies with lager sample size are needed to be conducted to explore the inconsistent result.…”
Section: Discussioncontrasting
confidence: 59%
“…There are three articles about the association between rs2069837 and cancer risk, and their results consistently showed that the rs2069837-AA genotype was a protective factor for cervical cancer and hepatocellular carcinoma, one study found that rs2069837 were related to the IL6 expression level in cervical tissues. [36–38]. In our study the results were not statistically significant, further studies with lager sample size are needed to be conducted to explore the inconsistent result.…”
Section: Discussioncontrasting
confidence: 59%
“…However, Grimm et al failed to detect relationship between IL-6 -174G>C polymorphism and the risk for cervical cancer [ 27 ]. A recent study by Pu et al [ 26 ] found that cervical cancer risks were significantly higher in carriers of C allele of rs1800795 polymorphism than those with GG genotype. By now, only one meta-analysis by Liu et al [ 30 ] was conducted to explore the association between IL-6 -174G>C and cervical cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies suggested that IL-12B rs3212227 and IL-6 rs1800795 polymorphisms are associated with an increased risk of cervical cancer. However, two recent meta-analyses were performed to evaluate IL-12B rs3212227 and IL-6 rs1800795 polymorphisms with cervical cancer risk and their results indicated that no significant association was found among all ethnicities (Chang et al, 2015;Liu et al, 2017;Pu et al, 2016;Zheng et al, 2017). Therefore, controversy and inconformity still remained about IL-12B rs3212227 and IL-6 rs1800795 polymorphisms and most of studies recruited a limited sample capacity, which is insufficient to get a firm conclusion about the associations of these polymorphisms with development of cervical cancer.…”
Section: Association Of Il-12b Rs3212227 and Il-6 Rs1800795mentioning
confidence: 99%